A new insight into multi-tier structure tailoring: Synchronous utilization of particle migration and incompatible interface separation under shear flow. (24th April 2020) - Huang, Yanhao; Chen, Libo; Zheng, Shaodi; Wu, Xiaotian; Liu, Lei; Ke, Kai; Liu, Zhengying; Yang, Wei; Yang, Mingbo
Abstract: In this work, polyethylene (PE)/silica microsphere composite melt is used to penetrate the ethylene-α-octene block copolymer (OBC) melt in multi-melt multi-injection molding (M 3 IM) process. Due to the viscosity difference between PE/silica composite melt and OBC melt, a disturbed flow interface of these two melts formed. Thanks to the "shear-induced migration" theory in suspended balance model (SB model) and the unique flow field in M 3 IM, silica microspheres can be designed to migrate from high shear rate layer to low shear rate layer in PE/silica core melt, further to intaglio micro-pits on the interface of PE/silica core and OBC skin melt. As a result, the migrated silica microspheres can be intuitively observed by peeling off the OBC layer, as well as a "lotus seedpod"-like structure consisting of quantity-adjustable asperities and micro-pits can be constructed on the peeled surface of OBC layer. This work sheds lights to rapidly fabricate multi-tier structures by polymer melt processing strategies, aiming to manufacture functional devices on a large scale. Graphical abstract: Image 1 Highlights: Silica microspheres have been promoted to migrate and jam at the interface of PE and OBC layers during the M 3 IM process. A "lotus seedpod"-like structure consisting of micro-scale asperities and micro-pits has been constructed on OBC layer. The morphology of the "lotus seedpod"-like structure can be regulated by adjusting the content of silica in PE core melt.